The Nuffield Physics Ordinary-level Curriculum Project in the 1960s: a Transnational Project? (Foro de Educacion, 2020)
The Nuffield Physics curriculum project was the first national curriculum project held in the UK. The Ordinary-level Nuffield physics project, developed between 1962 and 1966 for academic pupils in grammar schools, was one of the most interesting and innovative projects of the 1960s. It had many transnational features, with influences of ideas and practices running across national borders, as well as national characteristics. It owed many of its distinctive ideas around physics for the inquiring mind to Eric Rogers, and ultimately to the progressive school Bedales in the 1920s and 1930s, as well as American reform under the banner of the Physical Science Study Committee. These were played out at a local level, for example in Worcester, led by Ted Wenham and John Lewis. During and after the project, although there was some resistance to sharing these ideas as they developed, key figures began to engage with other national systems and projects in spreading the word about Nuffield physics. Transnationalism was at the heart of the significance and achievements of Nuffield O-level physics, no less than of its problems and limitations.